Sensitometry of Diazo Papers (I): Spectrosensitivity Measurement of Diazo Papers - KUNITOMO, Yoshihisa; NAKAGAWA, Yasuo (The Journal of The Society of Scientific Photography of Japan, 1962)
Measurement of the spectral sensitivity of diazo paper, with monochromatic light that is given by combination of bright line spectrum of mercury lamp, cut-off filter and band-pass filter, is described in this paper. On two diazo papers used, maximum sensitivity wave length is approximately 4000Å, and the range of sensitivity is about 3000-4500Å. It has conformed to the spectral absorption characteristics of diazo materials. For 3650A radiation, given density 0.19 (at 5500Å), the absolute sensitivity of diazo papers has been 0.05-0.07 jule/cm2 and 0.09-0.11 jule/cm2 at 20C°.